MODEL KERUKUNAN SOSIAL PADA MASYARAKAT MULTIKULTURAL CINA BENTENG (KAJIAN HISTORIS DAN SOSIOLOGIS) - Muhamad Arif (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2014)
This study was conducted to gain an overview of the historical and sociological perspective of the model of social harmony in a multicultural society of Cina Benteng, Tangerang. It used descriptive qualitative research method using an inductive approach in conducting the analysis. Data collection techniques mainly emphasize on library research techniques, interview, observation, and documentation. There are two important c onclusions generated in this study. The fi rst, models of social cohesion in a multicultural society of Cina Ben teng has historically formed since their arrival in the watershed Cisedane. Historical process has made Cina Ben teng society has a unique blend, namely their persistence in holding the customs of their ancestors already hundreds of years old, as well as their fl exibility to enable them to carry out the process of amalgamation, assimilation, and acculturation with the local community and culture as well. Second, in a sociological perspective, the model of social harmony in Cina Benteng society is not just happening in the fi eld of art, but also occurs in settle ment patterns, language of communication, traditional wedding procession, traditional clothes, gambang kromong musi c, and cokek dance.